Effect of Different Levels of the Processed Lablab purpureus Seeds on Laying Performance, Egg Quality and Serum Parameters - Ragab , H.I.; Ati, K.A. Abdel; Kijora, C.; Ibrahim, S. (International Journal of Poultry Science, 2012)
L. purpureus is considered to substitute some of conventional plant protein sources in poultry diets. In 12 weeks feeding trial the processed L. purpureus seeds were investigated for its impacts on laying performance, egg quality and serum constituents of Hisex White hens. Diets contain 0, 5, 10, 15 and 20% L. purpureus were allotted randomly following completely randomized design to 25 units of three birds each. Hen day egg production, egg weight, egg mass, FCR and weight gains were significantly (p